Análisis de la impedancia de salida en lazo cerrado de inversores funcionando en modo isla, utilizando esquemas droop - Trujillo Rodríguez, César Leonardo; Velasco de la Fuente, David; Figueres Amoros, Emilio; Garcera Sanfeliu, Gabriel; Ortega Gonzalez, Ruben (Ingeniería, 2008)
In this paper the island mode condition is analysed. The island mode refers to a microgrid that is not connected to the electrical grid and the inverters have to operate as a voltage source in parallel with others equipments of similar characteristics. This study focuses on how to interconnect the inverters without using any type of communication, by using droop schemes. First, an analisys is performed on how to obtain a certain value of output impedance by using an impedance loop. Then, we propose to use physical characteristics of the inverter and the type of controller to achieve results similar to those obtained by the impedance loop. In order to validate this analysis, simulations on parallel connection of several inverters supplying power to load are performed. Lastly some conclusions are presented.